The Regulations of the Supervisory Officer Personal Data Protection-Based Accountability Principle - Wardah Yuspin; Trisha Rajput; Abhinayan Basu Bal; Kelik Wardiono; Absori Absori (BESTUUR, 2024)
This study examines The Model of Regulations Supervisory Officer Personal Data Protection-Based Accountability Principle: Lessons from Sweden. This study is a qualitative approach by reviewing and analyzing legal aspects and comparing laws. Even though Indonesia has a personal data protection law, misuse of personal data is still excessive. Owing to accountability basis PDP supervision arrangements have not been properly implemented. Meanwhile, Sweden was chosen as a comparison country since it was one of the first countries to have a personal data protection law. The result shows that in Sweden, personal data is regulated in the General Data Protection Regulation and the personal data supervisor well implemented the principle of accountability therefore it worked effectively. Meanwhile in Indonesia, given that a data protection supervisor has not been established, Protection of personal data is still carried out by each agency appointed by law on a sectoral basis and it deemed less effective in providing personal data protection. Therefore, the personal data supervisor with a single rule and direct responsibility to the president is the perfect model for Indonesia.